2021
DOI: 10.5539/res.v13n1p103
|View full text |Cite
|
Sign up to set email alerts
|

Flattening the Hierarchy Curve: Adaptive Leadership during the Covid-19 Pandemic – A Case Study in an Academic Teacher Training College

Abstract: The Covid-19 pandemic forced institutions of higher education to adopt agile leadership behaviors. The current research aims to examine how the leadership at the Ohalo teacher training college in Israel dealt with the crisis caused by the pandemic. The research hypothesis, predicting a positive relationship between the college leadership’s decisions and lecturers’ positive evaluations regarding these decisions, was confirmed. Previous research has given scant attention to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The leadership style described by our participants involved a 'flattening of the hierarchy' with regular, reciprocal, and co-operative communication. Such adaptive leadership styles have been recognised as important for ensuring the continued functioning of academic institutions during the COVID-19 pandemic [51].…”
Section: Discussionmentioning
confidence: 99%
“…The leadership style described by our participants involved a 'flattening of the hierarchy' with regular, reciprocal, and co-operative communication. Such adaptive leadership styles have been recognised as important for ensuring the continued functioning of academic institutions during the COVID-19 pandemic [51].…”
Section: Discussionmentioning
confidence: 99%
“…By directing their attention to intricate processes of collaboration and exploring solutions for problems "in order to construct an appropriate response" adaptive leadership can have a positive impact on HEIs [9]. Adaptive leadership assists collective leadership at all levels and across academic leadership structures like faculties, departments and professional support teams to "adjust to and thrive in challenging environments" [11]. These authors found that the pandemic caused both a crisis and realization among leaders of HEIs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These authors found that the pandemic caused both a crisis and realization among leaders of HEIs. They also found that changes and activities "based on broad, systemic thinking" were necessary to be driven by leadership but "undertaken by many people together" [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation